2019
DOI: 10.1089/neu.2018.5674
|View full text |Cite
|
Sign up to set email alerts
|

Novel Metabolomic Comparison of Arterial and Jugular Venous Blood in Severe Adult Traumatic Brain Injury Patients and the Impact of Pentobarbital Infusion

Abstract: Treatment of severe traumatic brain injury (TBI) in the intensive care unit focuses on controlling intracranial pressure, ensuring sufficient cerebral perfusion, and monitoring for secondary injuries. However, there are limited prognostic tools and no biomarkers or tests of the evolving neuropathology. Metabolomics has the potential to be a powerful tool to indirectly monitor evolving dysfunctional metabolism. We compared metabolite levels in simultaneously collected arterial and jugular venous samples in acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Levels of several amino acids, including BCAAs and their breakdown products, as well as threonine, alanine and serine, were decreased in patients with TBI, along with increasing severity of the injury. Although we did not observe significantly decreased levels of BCAAs in our previous study 18 , similar decreases in patients with TBI were observed in two other studies 20 , 50 , while alterations in levels of BCAA breakdown products have also been reported in cerebral microdialysis fluids of patients with TBI 51 . BCAAs 52 and serine 53 can easily pass from circulation to the brain across the BBB via their transporters, where they serve as important precursors of glutaminergic neurotransmission in astrocytes.…”
Section: Discussionsupporting
confidence: 79%
“…Levels of several amino acids, including BCAAs and their breakdown products, as well as threonine, alanine and serine, were decreased in patients with TBI, along with increasing severity of the injury. Although we did not observe significantly decreased levels of BCAAs in our previous study 18 , similar decreases in patients with TBI were observed in two other studies 20 , 50 , while alterations in levels of BCAA breakdown products have also been reported in cerebral microdialysis fluids of patients with TBI 51 . BCAAs 52 and serine 53 can easily pass from circulation to the brain across the BBB via their transporters, where they serve as important precursors of glutaminergic neurotransmission in astrocytes.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, this review found that after sTBI, serine [ 32 34 ], alanine [ 32 , 33 ], proline [ 26 , 29 , 34 ], valine [ 27 , 35 ], and leucine [ 27 , 35 ] all decreased, while conflicting results were found for methionine [ 29 , 30 ]. Choline presented conflicting results as well, but more studies declared an increase in choline following sTBI [ 25 , 29 , 34 ]. Inositol [ 36 ] and myo-inositol [ 32 ] were also found to increase after sTBI, while n -acetylaspartate [ 25 , 28 ] and citrulline [ 26 , 34 ] were found to decrease.…”
Section: Resultsmentioning
confidence: 99%
“…However, the number of metabolites potentially detectable are lower than in our study, for technical limitations. Other studies have focused on the use of plasma metabolomics in TBI management [21, 22], even using cerebrospinal fluid [23] or urine [24] as the sample of reference. Similarly, in a case-control approach, other researchers indicate that a low number of metabolites, one of them stearic acid, allowed for differentiation of TBI from controls, and even helped to classify TBI patients according severity [25].…”
Section: Discussionmentioning
confidence: 99%